Architectural Mediation Between Islam And Local Culture In Lombok’s Vernacular Mosques: The Case of Gunung Pujut and Gumantar - Ernawati, Atie; Mariana, Diah; Hapsari, Ambar Tri; Irfansyah, Puput; Bachtiar, Yogi; Zulkarami, Achmad (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
This study investigates how vernacular mosque architecture in Lombok functions as a mediating system between Islamic doctrine and Sasak local culture. Focusing on the Gunung Pujut and Gumantar Mosque, the research examines how architectural elements translate religious principles into culturally grounded spatial forms and how this mediation contributes to cultural resilience amid modernization. Using a qualitative approach, data were collected through architectural documentation and in-depth interviews with Tuan Guru, Tokoh Adat, and the local community. The findings demonstrate that the integration of Islam and local culture is structurally embedded through a hierarchical architectural system comprising the head, body, and foundation, which reflects both Islamic spiritual stages and Sasak cosmology. Key elements such as the saka guru pillars operate as material mediators that embody Islamic ethics of humility, moderation, and communal balance. Furthermore, vernacular mosque architecture is shown to sustain Sasak Muslim identity by enabling adaptive continuity amid architectural homogenizations. This study contributes to Islamic architectural discourse by extending Critical Regionalism through an ethno-Islamic perspective that recognizes vernacular forms, materials, and construction logic as legitimate expressions of Islamic values and cultural resilience.